Traffic Utilization on Internet Application: Trends and Impact in Student Wireless Network - Noraniah, Abdul Aziz; Che Yahaya, Yaakub; Hanipah, M. M. (AENSI Publishing, 2014)

(untitled)
Understanding trends and impact of utilization on Internet application is critical for those who develop, deploy, and manage wired and wireless network. This study has taken place at TATI University College (TATIUC) in student wireless network.The effectiveness of student wireless network operations has been disrupted resulting in degradation of network performance. In order to sustain its network effectiveness, traffic analysis has been conducted to figure out bandwidth utilization on Internet application. The hardware-based network monitoring tool is used in this study which is focused only on network VLAN 300. Monitoring was conducted for seven consecutive days in the academic semester. The main data was captured from the monitoring tool included attribute on application flow based on number of active user, flow pattern based on application type and percentage of application type consumed on designated bandwidth.Overall, this study shows user behavior on the application in which more than 95% of the student population uses the network connection and contributes to 50% of consumption to the Web Browsing Application, 21% of the Intelligent Domain Identification application and 20% to the HTTP File Download application on average.